Immune thrombocytopenic purpura cases following COVID-19 vaccination. - Annalisa Condorelli; Uros Markovic; Roberta Sciortino; Mary Ann Di Giorgio; Daniela Nicolosi; Gaetano Giuffrida (Mediterranean Journal of Hematology and Infectious Diseases)
Not requested.